“Hey Siri, Help Me Take Care of My Child”: A Feasibility Study With Caregivers of Children With Special Healthcare Needs Using Voice Interaction and Automatic Speech Recognition in Remote Care Management - Sezgin, Emre; Oiler, Brannon; Abbott, Brandon; Noritz, Garey; Huang, Yungui (Frontiers in Public Health, 2022)
Background: About 23% of households in the United States have at least one child who has special healthcare needs. As most care activities occur at home, there is often a disconnect and lack of communication between families, home care nurses, and healthcare providers. Digital health technologies may help bridge this gap. Objective: We conducted a pre-post study with a voice-enabled medical note-taking app in a real world setting with caregivers (parents, family members) of children with special healthcare needs (CSHCN) to understand feasibility and effectiveness of voice interaction and automatic speech recognition (ASR) for medical note-taking at home. Methods: Forty-one parents of CSHCN were recruited through convenience sampling. Participants completed a pre-study survey collecting demographic details, technology and care management preferences. 24 participants completed the study, using the app for 2 weeks and completing an exit survey. The app facilitated caregiver note-taking using voice interaction and ASR. We assessed the feasibility of the app by descriptively analyzing survey responses and user data following the key focus areas of acceptability, demand, implementation and integration, adaptation and expansion. Perceived effectiveness was assessed by comparing perceived changes in mobile app preferences among participants. Voice data, notes, and transcriptions were descriptively analyzed. Results: Among those completed the post-study survey, approximately 80% of the caregivers agreed or strongly agreed that using the app would enhance their performance in completing tasks, the app is free of effort, and they would use the app in the future. In total, 88 voice interactive patient notes were generated with the majority of the voice recordings being less than 20 seconds in length. Most noted symptoms and conditions, medications, treatment and therapies, and patient behaviors. More than half of the caregivers reported that voice interaction with the app and using transcribed notes positively changed their preference of technology to use and methods for tracking symptoms and health events at home. Conclusions: Voice interaction and ASR use in mobile apps are feasible and effective in keeping track of symptoms and health events at home. Future work is suggested towards using integrated and intelligent systems with voice interactions with broader populations.